Análisis del proceso de compra del consumidor de la ciudad de Loja según el fundamento de Maslow en las necesidades del consumidor. - Jumbo Cevallos, Noelia del Carmen (2024)
This research project focuses on the analysis of consumer behavior in Loja city, specifically those between the ages of 28 and 65, using Maslow's methodology to analyze their consumption. A non-probabilistic convenience sampling technique was used, and a sample size of 384 surveys was determined, based on data from the last INEC population census in 2010 and a population growth rate of 2.05%. The research design is exploratory and descriptive, and tools such as surveys and IBM SPSS software will be used for data analysis. The objective is to describe, characterize and relate the consumer buying process according to Maslow's needs, the research problem focuses on the lack of implementation of appropriate marketing strategies by companies to meet the needs of customers, which vary and become more complex over time. Maslow's pyramid theory is used as a basis for understanding these needs and how they influence the consumer buying process; it was identified́ that most of the companies in the city of Loja are family businesses that do not meet customer expectations due to the lack of adequate marketing strategies. The study seeks to fill this information gap and provide an analysis based on Maslow's methodology to help companies make more informed decisions and improve their competitiveness and market positioning.